Passive design approach towards energy efficient building envelope for individual residential - Ahmad Shah, Fathihah (2015)
Energy issues are very important nowadays, due to possibility of energy shortage in the future with the increasing population and living standards. The concern over the need to reduce energy consumption is growing that influenced awareness rapidly increases and it encourages the implementation of green building worldwide. This study focuses on pattern of passive design approach for building envelope in term of energy efficiency for individual residential. Individual residential especially bungalows were selected case study due to various approach of design philosophies for cooling factor in designing building envelope. In the reality, certainly undeniable that the practice on energy efficiency of building envelope design is crucial. Building envelope is a critical component of the building that serves as the outer shell or a protector to the user and building itself. This study describes an investigation of the effect of six passive design strategies on building envelope design, namely site planning and orientation, daylighting, façade design, strategic landscaping, renewable energy and natural ventilation. Calculation of Overall Thermal Transfer Value (OTTV) act as a tool to determine building envelope performance and it will identify whether the building fulfill the requirement of energy efficient or not. Based on the guideline in Malaysian Standard, Code of Practice on Energy Efficiency and Use of Renewable MS 1527(2007), OTTV of the selected building should be not exceed 50W/m2. In conclusion, this study outlines the preferred requirement of passive design approach for building envelope in term of energy efficiency for individual residential